The Principal’s Strategy In Changing Teachers Mind Patterns To The Quality Of Learning At SMK Muhammadiyah 1 Temon - Asnawi Wijayanto; Enung Hasanah (al-fikrah: Jurnal Manajemen Pendidikan, 2022)
This study aims to determine the extent of the principal's strategy in changing the teacher's mindset to improve learning quality. The method used in this research is the interview and documentation method. In processing the research results using Atlas. ti 8 software, the steps are to process the data obtained and then provide a code, classify the code that has been obtained according to the same meaning, then combine several concepts that have the sense to get a new idea. The results of this study are the principal in changing the mindset of teachers by carrying out teacher training and implementing teacher competency development and teachers improving the quality of learning by using learning technology, learning media, and learning evaluation.